'Reference composition' not 'lead compound': recent developments in case law for obviousness of pharmaceutical composition claims. (September 2012) - Highlander, Steven L; Voges, Mark H
For most chemical compound claims, the obviousness analysis begins with the identification of a 'lead compound'. Pursuant to a recent decision from the Federal Circuit, a similar framework is now applicable for pharmaceutical composition claims. In Unigene Labs v. Apotex (2011), the obviousness analysis for a claim covering a bioequivalent nasal spray was said to start with the identification of the 'reference composition'. The court reasoned that while a person of ordinary skill in the art would typically be motivated to develop a bioequivalent of a given US FDA-approved reference composition, such a new composition may still be non-obvious if the prior art does not teach which bioequivalent among a large number of possible formulations is the best or which ingredient(s) may be substituted for others. A review of the case law reveals that the "reference composition" framework is neither entirely new nor universally applicable to all obviousness challenges to pharmaceutical composition claims. Even so, the Unigene decision appears to signal the court's preference for this framework and will likely employ it wherever it is appropriate to do so.